A key role for ALD1 in activation of local and systemic defenses in Arabidopsis - Song, Jong Tae; Lu, Hua; McDowell, John M.; Greenberg, Jean T. (Wiley, 2004)
The Arabidopsis thaliana agd2-like defense response protein1 (ald1) mutant was previously found to be hypersusceptible to the virulent bacterial pathogen Pseudomonas syringae and had reduced accumulation of the defense signal salicylic acid (SA). ALD1 was shown to possess aminotransferase activity in vitro, suggesting it generates an amino acid-derived defense signal. We now find ALD1 to be a key defense component that acts in multiple contexts and partially requires the PHYTOALEXIN DEFICIENT4 (PAD4) defense regulatory gene for its expression in response to infection. ald1 plants have increased susceptibility to avirulent P. syringae strains, are unable to activate systemic acquired resistance and are compromised for resistance to the oomycete pathogen Peronospora parasitica in mutants with constitutively active defenses. ALD1 and PAD4 can act additively to control SA, PATHOGENESIS RELATED GENE1 (PR1) transcript and camalexin (an antimicrobial metabolite) accumulation as well as disease resistance. Finally, ALD1 and PAD4 can mutually affect each other's expression in a constitutive defense mutant, suggesting that these two genes can act in a signal amplification loop.
Keywords: PAD4; salicylic acid; systemic acquired resistance; camalexin; acd6-1; Arabidopsis